LUNA: Bridging communication with sign language translation - Awang Abu Bakar, Normi Sham; Yusof, Siti Zulaikha; Irfan, Muhammad Syabil (International Islamic University Malaysia, 2025)
This paper presents Learn, Unite, Network and Assist (LUNA) App, an assistive Internet of Things (IoT) system designed to facilitate two-way communication between individuals with hearing and speech impairments and the general public. The LUNA system integrates a smart glove embedded with flex sensors and an MPU6050 accelerometer to recognize hand gestures and translate them into real-time text displayed via a mobile application developed using Flutter. Beyond gesture recognition, LUNA includes a sign language learning module, GPS-based emergency location tracking, and video call functionality via WebRTC, enabling enhanced communication and user safety. Developed using the Scrum methodology, the system combines ESP32 microcontroller-based hardware with Firebase for real-time data handling. Experimental results demonstrate that LUNA achieves high accuracy and responsiveness, with gesture recognition response times ranging from 850 to 1200 milliseconds. This project represents a step toward inclusive communication by promoting mutual understanding and interaction between the disabled and non-disabled communities.